Surface oxidation behavior of spark plasma sintered AlCrCuFeMnWx high entropy alloys at an elevated isothermal temperature - Dewangan, Sheetal Kumar; Kumar, Devesh; Kumar, Vinod; Ahn, Byungmin (International Journal of Refractory Metals and Hard Materials, 2024)
The high-temperature surface oxidation behavior of high-entropy alloys (HEAs) with compositions of AlCrCuFeMnWx (x = 0, 0.05, 0.1, and 0.5) was studied at 800 °C as an isothermal temperature for 50 h. The high entropy alloys (HEAs) were synthesized by mechanical alloying (MA) followed by spark plasma sintering (SPS). This study focused on the effect of oxidation resistance properties with different elevated temperatures on the high entropy alloy over the surfaces. The XRD and Raman analysis confirmed the formation of various oxides like Al2O3, Cr2O3, Fe2O3, and CrO2 mainly. The HEAs follow the single-stage parabolic law at 800 °C. To achieve better resistance against the heat, rather than adding more amount of refractory elements. Consequently, AlCrCuFeMnWx HEAs showed excellent oxidation resistance at elevated temperatures in a specific amount of tungsten. Different values of mass gain, loss, and complex oxidation kinetics were observed for the varying W-containing HEAs. These alloys formed inhomogeneous oxide scales possessing different regions with porous oxide layers and some areas revealed thin oxide scales due to the formation of discontinuous Mn, Cr, and Al-rich scales evidence found through the SEM images. It is noted that complicated oxides formed considerably more frequently on the W0 alloy than on other alloys, indicating that the addition of tungsten in the presence of Cr may inhibit the growth of certain types of multiphasic oxides and prevent spallation.
Keywords: Elevated temperature; High entropy alloys; Highest temperature; Isothermal temperature; Oxide scale; Resistance properties; Spark plasma; Spark-plasma-sintering; Surface oxidation behavior; Synthesised; High entropy alloy; Mechanical alloying; Oxidation; Oxide scale; Spark plasma sintering